Essential oils of Mentha pulegium and Mentha rotundifolia from Uruguay - Lorenzo,Daniel (2002)
Essential oils obtained by hydrodistillation from leaves of Mentha pulegium L. and Mentha rotundifolia (L.) Huds. from Uruguay were analysed by GC-FID and GC-MS. Oxygen-containing monoterpenes were the main group of constituents in both oils. Pulegone, isomenthone and menthone were the major components in the oil of M. pulegium, whereas piperitenone oxide and (Z)-sabinene hydrate were the major ones in M. rotundifolia. Enantiomerically pure (-)-menthone, (+)-isomenthone, (+)-isomenthol, (-)-menthol and (+)-pulegone were detected by multidimensional gas chromatography in the case of M. pulegium oil.